Seasonal variations of transpiration efficiency coefficient of irrigated wheat. Issue 2 (February 2021) - Tfwala, Cinisani M.; Mengistu, Achamyeleh G.; Ukoh Haka, Imoh B.; van Rensburg, Leon D.; Du Preez, Chris C.
Abstract: Global diminishing water resources, especially due to climate change have serious impacts on evaporation (E) from the soil surface, transpiration (T) from plants (crops) and grain yield, which relates to water use efficiency of different crops. A study was conducted at Kenilworth over two wheat cropping seasons (2007 and 2008) with the objectives of: (i) evaluating the effect of soils and seasons on T, E and yield, and (ii) relating these parameters to transpiration efficiency coefficient. The treatments included two soil types and two soil surface treatments (bare and mulched), which were all replicated four times. Weekly irrigation was done using a surface drip system while maintaining the water table at a constant depth. Soil water content was monitored using a neutron probe. Neither soils nor seasons were found to significantly influence the partitioning of evapotranspiration (ET), and T varied from 74 to 76% of ET while E varied between 24 and 26%. Surface treatments caused significant differences in grain yield in both seasons. Reducing evaporative loss improves the water productivity of wheat, which has an important implication in dryland farming. Abstract : Evaporation; Transpiration; Water use efficiency; Transpiration efficiency coefficient